The Self-Esteem Among FPTP Students in Relation to Academic Stress and Academic Achievement - SITI NORZIAH ISMAIL; AGILESWARAN (Research in Management of Technology and Business, 2023)
Self-esteem affects the thinking process, emotions, desires, values and goals in a person. Academic stress and academic achievement could develop the negative impact to self-esteem of every student in the all over the world. This study aims to find out the impact of self-esteem relation to academic achievement and academic stress. A quantitative research approach and a cross-sectional research design have been used to collect data from FPTP students in the target population through an online survey adapted and adopted from the previous study and shows a high-reliability value and gets validation from the previous study the expert. In this research data were used from 320 respondents. Finding shows that self-esteem and academic achievement has strong relationship (r=0.560). Meanwhile, academic stress shows that (r=0.288) which means positive relationship towards self-esteem. This study also proves that self-esteem significantly impact on academic stress (r=0.314) and academic achievement (r=0.593). In conclusion, this research shows good way on the academic achievement and academic stress among university students to the stakeholders, the ministry of higher education, and especially UTHM to overcome impact of self-esteem among university students. As well as the government could identify their future generation sufferings that they are there to help to overcome any psychological issues.